Tinjauan Literature Analisis Pencegahan COVID-19 Pada Mahasiswa Kesehatan Melalui Pendekatan Health Belief Model - Febry Nola Odhia; Indah Laily Hilmi; Munir Alinu Mulki (Universitas Muhammadiyah Surakarta, 2023)
Coronavirus disease-19 is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which is characterized by severe acute respiratory distress. The spread of SARS-CoV-2 from human to human is the main source of transmission, so transmission becomes more aggressive. SARS-CoV-2 spreads through droplets expelled from coughs or sneezes. People who have had close contact with someone who has tested positive for Covid-19 are at increased risk of infection. Health actions for disease prevention can be assessed using the Health Belief Model (HBM). This review is the result of a review of several published articles that focus on factors that influence COVID-19 prevention behaviour based on the Health Belief Model. The research methodology used is in the form of literature review with reference sources from various sources, such as Science Direct, and Google Scholar related to the review topic.